Famine foods : plants we eat to survive - Minnis, Paul E. (University of Arizona Press, 2021)
"How people eat today is a record of food use through the ages, and 'Famine Foods' offers the first ever overview of the use of alternative foods during food shortages. Paul E. Minnis explores the unusual plants that have helped humanity survive throughout history. "--